A Needs Assessment for Graduate Specialization in Nursing Informatics - Heller, B.R. (1988)
Indicators of need and rationale for developing Nursing Informatics as a new area of graduate level specialization are discussed including results of research conducted to determine employment opportunities for graduates of such a program of study as well as the potential student applicant pool. The projected impact of this educational breakthrough is also addressed.